Genome-wide identification of PEBP gene family in pineapple reveal its potential functions in flowering - Zhang, Xiaohan; Ouyang, Yanwei; Zhao, Lei; Li, Ziqiong; Zhang, Hongna; Wei, Yongzan (Frontiers in Plant Science, 2023)
Phosphatidylethanolamine binding protein (PEBP) plays an important role in regulating flowering time and morphogenesis of plants. However, the identification and functional analysis of PEBP gene in pineapple (AcPEBP) have not been systematically studied. The pineapple genome contained 11 PEBP family members, which were subsequently classified into three subfamilies (FT-like, TFL-like and MFT-like) based on phylogenetic relationships. The arrangement of these 11 shows an unequal pattern across the six chromosomes of pineapple the pineapple genome. The anticipated outcomes of the promoter cis-acting elements indicate that the PEBP gene is subject to regulation by diverse light signals and endogenous hormones such as ethylene. The findings from transcriptome examination and quantitative real-time polymerase chain reaction (qRT-PCR) indicate that FT-like members AcFT3 and AcFT4 display a heightened expression level, specifically within the floral structures. The expression of AcFT3 and AcFT4 increases sharply and remains at a high level after 4 days of ethylene induction, while the expression of AcFT7 and AcMFT1 decreases gradually during the flowering process. Additionally, AcFT3, AcFT4 and AcFT7 show specific expression in different floral organs of pineapple. These outcomes imply that members belonging to the FT-like subfamily may have a significant impact on the process of bud differentiation and flower development. Through transcriptional activation analysis, it was determined that AcFT4 possesses transcriptional activation capability and is situated in the nucleus and peripheral cytoplasm. Overexpression of AcFT4 in Arabidopsis resulted in the promotion of early flowering by 6-7 days. The protein interaction prediction network identified potential flower regulators, including CO, AP1, LFY and SOC1, that may interact with PEBP proteins. This study explores flower development in pineapple, thereby serving as a valuable reference for future research endeavors in this domain.